Efeito da dieta hiperlipídica e uso de insulina oral no epitélio intestinal e tecido adiposo - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Introduction: Diabetes and obesity are correlated diseases that cause other comorbidities. Knowing the mechanisms of action and interaction of these diseases allows developing less painful and more effective technologies when compared to the use of subcutaneous injection of insulin. The intestinal epithelium has a special role as diseases and undergoes hypertrophy in conditions of hyperglycemia. The use of OI (oral insulin) improves physical parameters and morphologically changes the intestinal epithelium and adipose tissue, reversing changes generated in the conditions of hyperglycemia by the intake of HFD (high-fat diet). Methods: Pre-clinical interdisciplinary research, in which 48 male Wistar rats were kept for 60 days separated into four groups of 12 animals, being: Group 1 control (standard laboratory diet + water gavage); Group 2 (standard laboratory diet + OI); Group 3 (HFD + water); Group 4 (HFD + OI). Rat body weight, intestine weight (duodenum, jejunum and cecum) and fat (omental, retroperitoneal, epididimal and mesenteric), histology and histomorphometry of intestines and fat, mucosal and epithelial thickness and fasting intestinal glucose were analyzed. Results: Oral insulin reduces the gain of adipose tissue, body weight and intestinal weight in rats submitted to a high fat diet. The small intestine is sensitive to oral insulin and changes its epithelium according to diet and in the presence of insulin. Oral insulin supplementation proved to have an effect on 10 parameters analyzed in concomitant administration with HFD (body weight, adiposity index, reduced hypertrophy and increased adipocyte hyperplasia, reduced fasting glycemia, reduced intestinal weight, increased villus, reduction of ileum villus width, reduction of ileum villus area and reduction of the epithelium thickness from ileum); and demonstrated an effect on 2 parameters analyzed in concomitant administration with a standard diet (increase of the villus width of the ileum and an increase in the villus area of the ileum). HFD also had an effect on the sample, the body, intestinal and fat weight of the rats that received HFD was significantly higher than the group that received standard laboratory diets. Hypertrophy had noted in the adipocytes of rats that received HFD. Conclusions: OI has an effect on the intestinal epithelium and adipose tissue, which has shown to regress the changes resulting from HFD. Suggest that OI could promote a greater or even total regression of the changes caused by HFD. Suggest that OI has a cytoprotective effect on GIT and adipose tissue in the presence of HFD.
Keywords: Trato Gastrointestinal; Histologia; Diabetes mellitus; Obesidade; Gastrointestinal Tract; Histology; Diabetes mellitus; Obesity; CNPQ::CIENCIAS DA SAUDE